SEBARAN DAN LUAS HUTAN MANGROVE DI WILAYAH PESISIR TELUK PISING UTARA PULAU KABAENA PROVINSI SULAWESI TENGGARA - Tarigan, M. Salam (UI Scholars Hub, 2008)
Distribution and area of mangrove forest in Pising Bay coastal area North Kabaena Island Southeast Sulawesi. Researched of mangrove forest in Pising Bay, North Kabaena Island Southeast Sulawesi was carried out on April 2006. Data digital Landsat 7ETM+ parth/raw 113/064 was used for mangrove mapping. Classification method was done is multispectral supervised with artificial neural networks algortms. Analysis and data validation from field survey, it is estimated that distribution and areas of mangrove forest in Pising Bay, North Kabaena Island Southeast Sulawesi is 152.128 Ha. Mangrove in Pising Bay dominated by rhizophora apiculata, rhizophora mucronata; and the forest is relatively in good condition.